SHOULD SMOKING BE BANNED IN BARS, TAVERNS AND GAMING CLUBS? (Tufts Archival Research Center, 2007)
Marginalia; Document advertising the debate between proponents and opponents of smoking bans. States the position of each side and asks readers to write in with their position.